#### Answer

x=5

#### Work Step by Step

Simplifying
4(x + 2) = 30 + -1(x + -3)
Reorder the terms:
4(2 + x) = 30 + -1(x + -3)
(2 * 4 + x * 4) = 30 + -1(x + -3)
(8 + 4x) = 30 + -1(x + -3)
Reorder the terms:
8 + 4x = 30 + -1(-3 + x)
8 + 4x = 30 + (-3 * -1 + x * -1)
8 + 4x = 30 + (3 + -1x)
Combine like terms: 30 + 3 = 33
8 + 4x = 33 + -1x
Solving
8 + 4x = 33 + -1x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'x' to each side of the equation.
8 + 4x + x = 33 + -1x + x
Combine like terms: 4x + x = 5x
8 + 5x = 33 + -1x + x
Combine like terms: -1x + x = 0
8 + 5x = 33 + 0
8 + 5x = 33
Add '-8' to each side of the equation.
8 + -8 + 5x = 33 + -8
Combine like terms: 8 + -8 = 0
0 + 5x = 33 + -8
5x = 33 + -8
Combine like terms: 33 + -8 = 25
5x = 25
Divide each side by '5'.
x = 5
Simplifying
x = 5